Creative Potential in Science: Conceptual and Measurement Issues - Lubart, Todd; Kharkhurin, Anatoliy V.; Corazza, Giovanni Emanuele; Besançon, Maud; Yagolkovskiy, Sergey R.; Sak, Ugur (Frontiers in Psychology, 2022)
This paper examines the concept of creative potential as it applies in science. First, conceptual issues concerning the definition of creative potential are explored, highlighting that creative potential is a moving target, and measures of creative potential are estimates of future behavior. Then three main ways to detect creative potential are examined. First, a person’s previous accomplishments in science can be analyzed. These accomplishments can be regarded as predictors of future creative performance. Second, science talent competitions can help to detect creative potential in children and adolescents. There are particular types of talent competitions differing from each other by the extent of focusing on individual (e.g., Science Fairs) or collaborative (e.g., Science Olympiads) work. Third, to measure an individual’s creative potential, psychometric tools such as Creative Scientific Ability Test (C-SAT), Test of Scientific Creativity Animations for Children (TOSCAC), and Evaluation of Potential Creativity (EPoC) can be used. These tools are conceptualized in terms of two scientific activities: hypothesis generation and hypothesis testing. In a final section, these three types of measures are placed in a novel time-space framework as applied to creative potential. Suggestions for future work are also discussed.